Nora Seed’s Literacy as Self-Discovery in Matt Haig’s The Midnight Library - Fatimatuzzahroh Fatimatuzzahroh; Much. Koiri (CV. Ulil Albab Corp, 2026)
In the current period, identity crises and the pursuit of existential significance are becoming increasingly complex psychological issues, exacerbated by social media pressures and high productivity expectations. The Midnight Library by Matt Haig has been analyzed using a variety of psychological techniques, but no research has examined how literacy serves as a tool for self-discovery in the book. Using the framework of New Literacy Studies (NLS) and a systematic close-reading methodology, this study examines how literacy operates as a transformative mechanism for identity reconstruction in The Midnight Library. The conceptualization of life as a textual possibility, reflective literacy practices through critical evaluation, cross-discursive identity negotiation, and the protagonist's transition from a passive reader to an active writer of their own existence were the four main themes that emerged from the analysis. These results show how literary works can serve as models for transformational literacy practices that mediate self-formation and advance narrative identity theory and literacy studies.